Исторические предпосылки появления тюркских мaмлюков в Aббaсидском хaлифaте (Вестник КазНУ. Серия Востоковедения, 2017)
In this articlewas considered the history of appearance of Turkic Mamelukesin the Middle East and in particular in the Abbasid caliphate. Manyresearchers think that the first appearance of Turkic Mamelukes was in theIX century and is connected with political events in the Abbasid caliphate.By the end of the power of the Abbasid caliphate Turkic Mamelukes beganto appear in lands of the Middle East. They turned into the main militaryforce of Egypt and Syria, and had direct influence on political life of thecountries of this territory. Over time Mamelukes turned into the main militaryand political force of this region.